2021
DOI: 10.1155/2021/8301359
|View full text |Cite
|
Sign up to set email alerts
|

Speed Sensor‐Less Control System of Surface‐Mounted Permanent Magnet Synchronous Motor Based on Adaptive Feedback Gain Supertwisting Sliding Mode Observer

Abstract: Aiming at the problems of severe chattering and difficulty in low-speed operation of the surface-mounted permanent magnet synchronous motor (SPMSM) sensor-less speed control system based on the traditional sliding mode observer (SMO), this paper proposes a sensor-less control strategy of supertwisting sliding mode observer based on adaptive feedback gain (AFG-STA-SMO). This strategy combines the supertwisting algorithm (STA) with the equivalent feedback principle and designs an adaptive law to compensate for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In order to achieve trajectory tracking of an unmanned agricultural tractor, Matveev et al developed a nonlinear SMC control strategy, which showed a robust performance [ 20 ]. However, SMC has a significant drawback, namely chattering, and a number of methods have been proposed to effectively mitigate the chattering effect and to improve the robustness of the system [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve trajectory tracking of an unmanned agricultural tractor, Matveev et al developed a nonlinear SMC control strategy, which showed a robust performance [ 20 ]. However, SMC has a significant drawback, namely chattering, and a number of methods have been proposed to effectively mitigate the chattering effect and to improve the robustness of the system [ 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the development of rare earth materials and digital processors, permanent magnet synchronous motor, as a potential new energy power actuator, is increasingly applied in wind power generation, electric vehicles, and other fields [1,2,3]. The traditional PMSM vector control adopts double closed-loop control or three closed-loop control, and the most widely used is double closed-loop PI control, that is, the outer loop speed loop and the inner loop current loop both adopt PI controller.…”
Section: Introductionmentioning
confidence: 99%
“…PMSM has been widely used in industry because of its high control accuracy and high-power factor [1,2,3,4,5].…”
Section: Introductionmentioning
confidence: 99%